1. factor using trial by error (x-2)(x-3)+0, set both factors equal to 0: x-2=0, x-3=0, solve and you get x=2 and x=3, so your answer should look like this: 2 or 3.
2. this is a little more difficult, but possible
start like this: (2x-_) (x+_), you may have to switch the signs,
then find factors of 5, 5 and 1, plug them in where you think they go and see if it works, you should get (2x+1)(x-5), do the same thing i did for the first one to solve and get your answers.
3. I think you can do this one by yourself
2007-07-05 08:37:33
·
answer #1
·
answered by over-achiever 2
·
2⤊
1⤋
1.x^2-5x+6=0
(x - 3)(x + 2) = 0
x = 3, x = -2
2.2x^2-9x-5=0
(2x + 1)(x - 5) =
2x + 1 = 0 >> 2x = -1 >> x = -1/2
x - 5 = 0 >> x = 5
3.3x^2+5x-2=0
(3x - 1)(x + 2) = 0
3x - 1 = 0 >> 3x = 1 >> x = 1/3
x + 2 = 0 >> x = -2
2007-07-05 08:30:46
·
answer #2
·
answered by Runa 7
·
0⤊
0⤋
(x - 2)(x - 3)= 0 x = 2 or 3
(2x +1)(x - 5) =0 x=-1/2 or 5
(3x - 1)(x + 2) =0 x = 1/3 or -2
2007-07-05 08:29:02
·
answer #3
·
answered by miggitymaggz 5
·
1⤊
0⤋
1.x^2-5x+6=0
(x-2)(x-3)=0
x=2, 3
2.2x^2-9x-5=0
(2x+1)(x-5)
x=-1/2, 5
3.3x^2+5x-2=0
(3x-1)(x+2)=0
x=1/3, -2
2007-07-05 08:37:28
·
answer #4
·
answered by zohair 2
·
1⤊
0⤋
x² - 5x + 6 = 0
x² - 3x - 2x + 6 = 0
x(x - 3) - 2(x - 3) = 0
(x - 2)(x - 3) = 0
- - - - - - - - -
2x² - 9x - 5 = 0
2x² - 10x + x - 5 = 0
2x(x - 5) + 1(x - 5) = 0
(2x + 1)(x - 5) = 0
- - - - - - - -
3x² + 5x - 2 = 0
3x² + 6x - x - 2 = 0
3x(x + 2) - 1(x + 2) = 0
(3x - 1)(x + 2) = 0
- - - - - - - - -s-
2007-07-05 09:31:09
·
answer #5
·
answered by SAMUEL D 7
·
1⤊
0⤋
1.x^2-5x+6=0
(x-6)(x+1)=0
so x= 6 or -1
2.2x^2-9x-5=0
(x-5)(2x+1)=0
x= 5 or -1/2
3.3x^2+5x-2=0
(x+2)(3x -1)=0
x = -2 or 1/3
2007-07-05 08:27:12
·
answer #6
·
answered by sweet n simple 5
·
0⤊
3⤋
1. (x-3) (x-2)
2. (2x+1) (x-5)
3. (3x+1) (x+2)
2007-07-05 08:29:48
·
answer #7
·
answered by Muaranah 3
·
0⤊
2⤋
1.(x-3)(x-2)
2.(2x+1)(x-5)
3.(3x-1)(x+2)
2007-07-05 08:37:56
·
answer #8
·
answered by mathewqarlati 1
·
1⤊
0⤋